Study on the interaction between different pathogens of Hand, foot and mouth disease in five regions of China - Yang, Zimei; Rui, Jia; Qi, Li; Ye, Wenjing; Niu, Yan; Luo, Kaiwei; Deng, Bin; Zhang, Shi; Yu, Shanshan; Liu, Chan; Li, Peihua; Wang, Rui; et al. (Frontiers in Public Health, 2022)
Objectives This study aims to explore the interaction of different pathogens in Hand, foot and mouth disease (HFMD) by using a mathematical epidemiological model and the reported data in five regions of China. Methods A cross-regional dataset of reported HFMD cases was built from four provinces (Fujian Province, Jiangsu province, Hunan Province, and Jilin Province) and one municipality (Chongqing Municipality) in China. The subtypes of the pathogens of HFMD, including Coxsackievirus A16 (CV-A16), enteroviruses A71 (EV-A71), and other enteroviruses (Others), were included in the data. A mathematical model was developed to fit the data. The effective reproduction number (Reff) was calculated to quantify the transmissibility of the pathogens. Results In total, 3,336,482 HFMD cases were collected in the five regions. In Fujian Province, the Reff between CV-A16 and EV-A71&CV-A16, and between CV-A16 and CV-A16&Others showed statistically significant differences (P < 0.05). In Jiangsu Province, there was a significant difference in Reff (P < 0.05) between the CV-A16 and Total. In Hunan Province, the Reff between CV-A16 and EV-A71&CV-A16, between CV-A16 and Total were significant (P < 0.05). In Chongqing Municipality, we found significant differences of the Reff (P < 0.05) between CV-A16 and CV-A16&Others, and between Others and CV-A16&Others. In Jilin Province, significant differences of the Reff (P < 0.05) were found between EV-A71 and Total, and between Others and Total. Conclusion The major pathogens of HFMD have changed annually, and the incidence of HFMD caused by others and CV-A16 has surpassed that of EV-A71 in recent years. Cross-regional differences were observed in the interactions between the pathogens.